Endoscopic Management of a Distal Ileal Foreign Body in a Child with Developmental Delay - A Case Report - Lenagala, Anuradha; Samarasena, Jeewan (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Foreign body ingestion is a common problem in the paediatric age group, with most cases involving the upper gastrointestinal tract. Foreign bodies that pass through the oesophagus can be safely observed. Impaction in the bowel can cause intestinal obstruction or perforation. Complicated foreign bodies can be retrieved either surgically or endoscopically. Case: A 4-year-and-6-month-old girl with multiple medical conditions presented four days after the ingestion of two foreign bodies (Hair pins). The child was irritable and experienced a vague lower abdominal pain, which was more pronounced in the right iliac fossa (RIF). With conservative management and a rectal enema one foreign body passed with stool. Over the next day she exhibited increasing distress and worsening RIF tenderness. Colonoscopy without air insufflation revealed an impacted foreign body in the distal ileum about 10cm from the ileocecal valve. Successful retrieval improved her clinical status, and she was discharged two days later. Discussion: Blunt foreign bodies that passed beyond the duodenum require intervention only if they fail to pass in a standard time frame or if a complication arises. Initial conservative management was attempted as she did not have features of generalized peritonism. However, colonoscopy was performed due to worsening distress and localized peritoneal signs, especially given her complex medical background. The procedure was conducted without gas insufflation to avoid pneumoperitoneum in the event of a potential intestinal perforation. Successful retrieval alleviated her clinical symptoms. Conclusion: Colonoscopy with ileal intubation is an effective method for retrieving impacted distal ileal foreign bodies in patients with localized peritoneal signs.